2000
DOI: 10.1243/1350650001543223
|View full text |Cite
|
Sign up to set email alerts
|

Lubricant thermal conductivity and heat capacity under high pressure

Abstract: The thermal conductivity ë and the heat capacity per unit volume, rc p , have been measured for a number of common lubricating oils. The oils tested were paraffinic and naphthenic mineral oils and a 50=50 blend of these. Poly-á-olefin, polyglycol, Santotrac, ester and rapeseed oils have also been tested. The measurements, using the transient hot-wire method, were carried out under isothermal conditions over a pressure range from atmospheric to 1.1 GPa and at two temperatures, 295 and 380 K (22 and 107 8C respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 13 publications
2
58
0
6
Order By: Relevance
“…PB is commonly considered to be a Newtonian fluid, but at higher molecular weights, and 30 more importantly, at higher pressures, it is known to shear thin at the shear rates 31 encountered in this work [3] been observed [5,6]. Hence the behaviour observed with PB in this work is relevant to …”
mentioning
confidence: 70%
See 1 more Smart Citation
“…PB is commonly considered to be a Newtonian fluid, but at higher molecular weights, and 30 more importantly, at higher pressures, it is known to shear thin at the shear rates 31 encountered in this work [3] been observed [5,6]. Hence the behaviour observed with PB in this work is relevant to …”
mentioning
confidence: 70%
“…It can become viscoelastic, and in some cases it may 26 even display glassy behaviour [4]. It has been shown that lubricants can solidify [5,6] at 27 pressures commonly encountered in EHL applications. These observations suggest that 28 the commonly assumed linear velocity profile may be inappropriate.…”
mentioning
confidence: 99%
“…If the film is assumed to form a central shear plane, a value 4 is obtained [32]. If the fluid shears mainly close to the walls, as recently observed using fluorescence for polybutene [33], then, at the limit, the second term in Eq. 6 becomes negligible since heat is generated at the solid surfaces.…”
Section: Temperature Effectmentioning
confidence: 85%
“…The temperature and pressure dependency of the thermal conductivity ( ) and heat capacity per volume ( , • )( , ) are based on the models of Larsson and Andersson [20]. Thereby, different parameters are available for different types of lubricant.…”
Section: Temperature and Pressure Dependency Of Lubricant Propertiesmentioning
confidence: 99%